Review: radiation-induced surface modification of polymers for biomaterial application - Jaganathan, Saravana Kumar (Springer Netherlands, 2015)
The field of biomaterials is one of the fast growing and continuously dominating in medical arena for the last five decades. Biomaterials utilize various kinds of materials ranging from metals, polymers, ceramics and biological substances as an alternative for replacing/assisting the functions of different parts of human system. Major issues associated with biomaterials are their properties and the biocompatibility which have to be addressed and resolved before promoting it to the market or clinical setting. In this scenario, polymers have emerged as a better candidate with versatile properties that make them ideal choice for biomedical applications. However, still the problem of biocompatibility limits the use of polymers in the human body. Several surface modification strategies are continuously evolving to improve the biocompatibility of polymers. This review initially outlines the polymers’ biomedical applications and also elicits the immune aspects of biocompatibility. Further, a thorough attempt is made to summarize the radiation-induced surface modification of the polymers. This review will help us to keep abreast of the recent advances in the radiation-induced surface modification and also in promoting radiation as a probable candidate to enhance the biocompatibility of polymers.